1999
DOI: 10.1177/109258729900400102
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Visitors’ Reactions to Interpretation in Australian National Parks

Abstract: Interpretive services are accepted elements of recreational experiences in natural areas. But what do we really know about the effectiveness of interpretation? By evaluating their services through well-planned visitor research, interpreters can better focus on enriching visitors’ experiences. This paper presents findings from three Australian studies into visitors’ reactions to interpretation. At Kakadu National Park, guided activities provided more immediate responses to visitors’ questions on Aboriginal art … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Indeed, public outreach in the form of park interpretation can inform policy and planning, and promote environmental leadership and stewardship. Therefore, in order to guide interpretive programming, it is important to evaluate the effectiveness of interpretation programs in reaching these goals (Beckmann, 1999; Hvenegaard et al., 2009). In general, there is a small but growing body of research on visitors’ awareness and use of interpretive programs on a park or system-wide basis, but little outside of Australia, United Kingdom, and United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, public outreach in the form of park interpretation can inform policy and planning, and promote environmental leadership and stewardship. Therefore, in order to guide interpretive programming, it is important to evaluate the effectiveness of interpretation programs in reaching these goals (Beckmann, 1999; Hvenegaard et al., 2009). In general, there is a small but growing body of research on visitors’ awareness and use of interpretive programs on a park or system-wide basis, but little outside of Australia, United Kingdom, and United States.…”
Section: Introductionmentioning
confidence: 99%
“…More than 50 years later, Ham (2009) examined Tilden’s claims from theoretical research within the fields of cognitive and social psychology and concluded that Tilden’s claims have considerable merit. To guide programming and investment, it is important to critically evaluate the effectiveness of interpretive activities in achieving these outcomes (Beckmann, 1999). Only in the last 20 years have researchers critically examined if and how the many goals of park interpretation have been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have argued that the intangible, abstract, and emotional connections inspired by interpretation cannot be captured by traditional evaluation approaches (Dustin & McAvoy, 1985). Other authors have lamented that evaluation efforts rarely probe visitor understanding of key messages and the influence of these messages on visitor beliefs (Beckmann, 1999;Hughes et al, 2009). Studies that have demonstrated quantifiable, concrete, interpretation-mediated changes in visitor knowledge, attitudes, and behavior have focused on the complete experience and not specific delivery methods (e.g., Powell & Ham, 2008;Zeppel & Muloin, 2008).…”
mentioning
confidence: 99%
“…A number of current studies provide data that support the immediate retention of information and impact of interpretation programs. This work has primarily been focused on immediate postsurveys, questionnaires, and/or immediate postinterviews (Beckman, 1999;Brody, Tomkiewicz, & Graves, 2002;Madin & Fenton, 2004;Morgan, Absher, Louden, & Sutherland, 1997;Porter & Howard, 2002;Povey & Rios, 2002). This focus on immediate data has recently been noted as a limitation in the field of interpretation because of the lack of breadth and depth that the queries provide (Koran, Willems, & Camp, 2000).…”
Section: Review Of Literaturementioning
confidence: 99%
“…An understanding of learning in informal settings will be of limited scope if the majority of research is conducted only in museums' ' (p. 11). This topic is further explained by Beckman (1999), who stated that ''if interpretation is an educational activity and if its objectives are educational in intent, then evaluation must clearly reflect the extent to which education or learning is achieved'' (p. 7). Additionally, the need for both short-term and long-term data is apparent to determine the credibility of interpretation techniques, particularly when the method is faced with an ever-increasing demand by the public for informal education programs (Packer & Ballantyne, 2002).…”
Section: Review Of Literaturementioning
confidence: 99%